Analisis Manajemen Risiko Berbasis ISO 31000, SWOT dan Matriks pada UMKM PD Berkah Rahayu - Muhamad Zaki; Afrian Insan Kamil; M Ramadhika Gautama K; Muhamad Luthfi Mubarok; Alfiana Alfiana (Indo Publishing, 2026)
This study aims to analyze risk management practices in the micro, small, and medium enterprise (MSME) PD Berkah Rahayu, which operates in the wood-cutting sector in Purwakarta Regency. A descriptive qualitative approach was used, supported by interviews and SWOT analysis, to identify internal and external factors influencing the business. The findings reveal four main categories of risks faced by the enterprise: market risk, operational risk, human resource risk, and financial risk. Market risks arise from fluctuating demand, changes in wood prices, competition with similar businesses, and dependence on local markets. Operational risks include machine damage, inconsistent cutting quality, and delays in raw material supply. Human resource risks are associated with limited skilled labor and lack of training, while financial risks relate to unstable cash flow and increasing operational costs. By applying the Risk Matrix and ISO 31000 principles, PD Berkah Rahayu is able to determine priority mitigation strategies, such as regular machine maintenance, employee competency improvement, strengthening supply chain management, and enhancing financial control. This study highlights the importance of structured risk management in improving sustainability, competitiveness, and operational effectiveness for MSMEs.